Statin use, survival and incidence of thrombosis among older patients with polycythemia vera and essential thrombocythemia - Nikolai A. Podoltsev; Rong Wang; Rory M. Shallis; Jessica M. Stempel; Mengyang Di; Natalia Neparidze; Amer M. Zeidan; Scott F. Huntington; Smith Giri; Sarah C. Hull; Steven D. Gore; Xiaomei Ma (Cancer Medicine, 2023)
Abstract Background Polycythemia vera (PV) and essential thrombocythemia (ET) are linked to increased risk of cardiovascular morbidity and mortality. In addition to the reduction in of arterial thrombotic events, statins may prevent venous thrombosis including among patients with cancer. As previous registry‐ and claims‐based studies revealed that the use of statins may improve the survival of patients with various malignancies we evaluated their impact on outcomes of older adults with PV and ET. Methods We identified 4010 older adults (aged 66–99 years at diagnosis) with PV (n = 1809) and ET (n = 2201) in a population‐based cohort study using the Surveillance, Epidemiology, and End Results‐Medicare database with median follow‐up of 3.92 (interquartile range: 2.58–5.75) years. Propensity score matching (PSM) and inverse probability of treatment weighting (IPTW) approaches were utilized to assess potential association between statins and overall survival. Multivariable competing risk models with death as a competing risk were used to evaluate possible relationship between statins and the incidence of thrombosis. Results 55.8% of the patients used statins within the first year after PV/ET diagnosis, and statin use was associated with a 22% reduction in all‐cause mortality (PSM: hazard ratio [HR] = 0.78, 95% confidence interval [CI]: 0.63–0.98, p = 0.03; IPTW: HR = 0.79, 95% CI: 0.64–0.97, p = 0.03). Statins also reduced the risk of thrombosis in this patient population (PSM: HR = 0.63, 95% CI: 0.51–0.78, p < 0.01; IPTW: HR = 0.57, 95% CI: 0.49–0.66, p < 0.01) as well as in PV and ET subgroups. Conclusions These findings suggest that it may be important to incorporate statins into the therapeutic strategy for older adults with PV and ET.